2009
DOI: 10.2147/ndt.s4048
|View full text |Cite
|
Sign up to set email alerts
|

Update on the use of memantine in Alzheimer’s disease

Abstract: Memantine is a low to moderate affinity N-methyl-D-aspartate receptor (NMDAR) antagonist. The effects of memantine in Alzheimer’s disease (AD) have been studied in 7 randomized controlled trials in many post-hoc analyses. Three out of four RCTs in patients with moderate to severe AD (Mini Mental State Examination [MMSE] <14) showed a statistically significant but clinically small positive effect of memantine on cognition, global functioning, activities of daily living (ADL) and neuropsychiatric symptoms. No ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 56 publications
1
70
0
1
Order By: Relevance
“…Memantine is a noncompetitive NMDA receptor antagonist and has been shown to have mild clinically relevant effects in moderate-to-severe AD (35). Riluzole inhibits the release of glutamate and also blocks some of the postsynaptic effects of glutamate (36).…”
Section: Discussionmentioning
confidence: 99%
“…Memantine is a noncompetitive NMDA receptor antagonist and has been shown to have mild clinically relevant effects in moderate-to-severe AD (35). Riluzole inhibits the release of glutamate and also blocks some of the postsynaptic effects of glutamate (36).…”
Section: Discussionmentioning
confidence: 99%
“…The C max at steady state of memantine ER in plasma was 127.1 ± 21.1 ng/mL which is approximately 3 to 4 times the C max reported for memantine 20 mg (22 to 46 ng/mL). 16,18 However, there was no direct relationship between the increased C max in the memantine ER study and increased adverse events. 16 …”
Section: Pharmacokinetic Profile Of Memantine Ir Vs Memantine Ermentioning
confidence: 94%
“…Long-term studies show good tolerability of memantine with an acceptable side-effect profile [41]. It must be concluded that memantine is a relatively safe drug with few side effects and neglectable risk of drug-drug interactions, but adverse drug reactions (ADRs) of memantine (Stop using memantine serious side effects: cough, chest tightness, fever, trouble breathing; chest pain, fast heart rate; confusion, hallucinations; sudden numbness or weakness, especially on one side of the body; lack of coordination; fainting or seizure (convulsions); urinating less than usual or not at) are found in clinical trials in mild to severe dementia [42]. The effectiveness and side effects of memantine might be determined by the hepatic clearance of caffeine or various drugs.…”
Section: Long-term Effects Of Combined Treatment With Memantine and Dmentioning
confidence: 99%